Richer of Saint-Remi - Lake, Justin (Book collections on Project MUSE., 2013)
Building upon, but also moving beyond, previous scholarship that has focused on Richer's political allegiances and his views of kingship, this study provides a comprehensive synthesis of the History, examining Richer's use and abuse of his sources, his relationship to Gerbert, and the motives that led him to write.